The impact of fangxian huangjiu on the fermentation quality and microbial community dynamics of cigar wrapper leaves - Yao, Lan; Zhang, Tongtong; Shan, Yule; Yang, Jingpeng; Yu, Jun; Yang, Chunlei; Chen, Xiong (Frontiers in Bioengineering and Biotechnology, 2024)
Cigar wrapper leaves (CWLs) plays a crucial role in reflecting cigar overall quality. Originating from the Qinba region of China, Fangxian Huangjiu (FHJ) is distinctive from other varieties of Huangjiu. To investigate the effects of FHJ on enhancing the aroma and quality of CWLs, as well as the consequent alterations in microbial communities, Gas Chromatography-Mass Spectrometry (GC-MS) coupled with Odor Activity Value (OAV) analysis was utilized to evaluate the volatile aroma components of CWLs. The results indicated that the total amount of aroma compounds in CWLs reached 3086.88 ug/g, increasing of 270.50% and 166.31% compared to the unfermented and naturally fermented groups, respectively. Among them, β-ionone and 4,7,9-megastigmatrien-3-one from the FHJ fermentation group significantly influenced the sensory characteristics of CWLs. Metagenomic results demonstrated that FHJ fermentation enriched the abundance of both shared and unique microbial species in CWLs, while also increased the diversity of differential microbial species. Addition of FHJ effectively altered the microbial community structure of CWLs from a dominance of Staphylococcus to a prevalence of Staphylococcus, Aspergillus, Pseudomonas, and Acinetobacter. The interactions among these diverse microorganisms collectively contribute to the enhancement of the intrinsic quality of CWLs. This paper provides a theoretical basis for improving the quality of CWLs by FHJ and exploring the changes of microbial community structure and interaction between CWLs and FHJ.